Perceptions On Communicative Language Teaching Approach Among Efl Primary School Teachers In Rural China - Yihan, Fang (2024)
Related studies are rarely associated with primary school teachers, whose experiences might be different from those at higher levels. To address this gap, a mixed-method study was administered to a group of rural primary school teachers in China to learn more about their perspectives and the challenges they faced when attempting to employ CLT in their classrooms.